Penonton Boys’ Love: Ketertarikan, Respon, dan Orientasi Seksual - Millah Ananda Yunita (Universitas Muslim Maros, 2022)
With the issuance of Minister of Health Regulation Number 9 of 2020 concerning Guidelines for Large-Scale Social Restrictions in the Context of Accelerating the Handling of Corona Virus Disease 2019 (Covid-19), the government recommended that all community activities be carried out from home (work from home). The amount of time spent at home causes people to become bored and need entertainment, one of which is by spending time to watch film. One of the shows that is currently booming is Boys' Love which is a fictional media (manga, anime, series) that focuses on homoerotic and homoromantic relationships between men. This article discusses how audiences are attracted to, respond to, and question their sexual orientation. Using qualitative approach, this study combined in-depth interview and observation as data collection methods. his research was conducted online through the brightforwin fanpage community which took place from August 2021 to February 2022. There are eleven informants involved in this study who are the audiences of Boys’ Love. They vary according to age (between 19 and 42 years), sex (eight women and three men), and status (three housewives and eight college students). The study shows that Boys' Love series became popular because it is not only focused on sexual activity, but also on how to build relationships between characters, to express sexuality, and to deepen relationships between viewers. The public's response to this series was varied, some were suddenly interested and became big fans of the Boys' Love series, some didn’t care, and others clearly reject this series. In regard to the sexual orientation of Boys' Love audience, there are differences between male and female audience. Male audience of Boys' Love series is considered as transgender or gay. For female audiences, there is a difference between married and single women. For married women, their sexual orientation is not questioned because of their marital status, while for single women, their orientation is questioned by others. But, as the fan and viewer of Boys’ Love some single men and women also question their sexual orientation.